MACROZOOBENTHOS DIVERSITY AND FUNCTIONAL FEEDING GROUP (FFG) IN BEREMBANG RIVER OF WEST KALIMANTAN - Wolly Candramila; Sisi Marda Lorensa; Yunike Pristalika; Junardi Junardi (Universitas Medan Area, 2022)
This study analyzes macrozoobenthos diversity and functional feeding group in Berembang River, Kubu Raya Regency, West Kalimantan. The obtained macrozoobenthos were identified to the genus level, and their functional feeding group was determined through a literature study. Data on diversity, evenness, and dominance were analyzed descriptively. Diversity (H') and Evenness (E) of macrozoobenthos in Berembang River were low (H'=0.73 and E=0.15) while Dominance (C) was high (C=0.81) as evidenced by a large number of genera Corbicula and Gammarus. Macrozoobenthos functional feeding groups found at both stations can be divided into six categories, namely shredders, gathering collectors, deposit feeders, sub-surface deposit feeders, filtering collectors, and scrapers.